Tourism in Africa - Christie, Iain (2012)
Governments in Africa are showing increasing interest in tourism as a source of growth and diversification. Recent work indicates that tourism in Africa can contribute effectively to economic development. The tourism industry throughout Africa often operates below international competitive standards, but several products already meet international standards of excellence. This Notes examines the government's role in ensuring economic, environmental, and cultural sustainability, poverty alleviation, and social inclusion.